A little note : IITJEE foundation maths


Solve 2(x^{2}-6)=3(x-4)


We have 2x^{2}-12=3x-12

that is, 2x^{2}=3x call this as Equation (1)

Transposing, 2x^{2}-3x=0


Hence, x=0, or 2x-3=0

Thus, the roots are 0 and \frac{3}{2}


In equation (1), above, we might have divided both sides by x and obtained the simple equation 2x=3, hence, x=\frac{3}{2}, which is one of the solutions of the given equation. But, the student must be particularly careful to notice that whenever an x, or a factor containing x, is removed by division from every term of an equation, it must not be neglected, since the equation is satisfied by x=0, which is therefore, one of the roots.

More on IITJEE foundation maths later,

Nalin Pithwa

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Google photo

You are commenting using your Google account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s

This site uses Akismet to reduce spam. Learn how your comment data is processed.

%d bloggers like this: